STRATEGI KOMUNIKASI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KOTA PEKANBARU DALAM PEDAMPINGAN ANAK KORBAN KEKERASAN SEKSUAL - Liany Wulan Asih; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Social issues became topics frequently discussed, such as poverty, corruption, crime and social disparities as well, as well as with various cases of violence which often happens lately, is sexual violence against children. One of the non profit institutions namely the Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) city of Pekanbaru has attempted to provide guidance on child victims of sexual violence both in the psychological accompaniment and legal accompaniment even with minimal budget. This research aims to identify the target of the communication, the communication of the message destination, the selection of communication media, and the role of the Communicator is used in Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) city of Pekanbaru in mentoring child victims of sexual violence.This research uses descriptive qualitative research methods, with the selection of the informant using the technique of purposive sampling. Informants in this study is the Vice Chair of the 1, counselors, psychologists, lawyers, and two parents of children victims of sexual violence ever conducted by the Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) city of Pekanbaru. Using data collection techniques of observation, interview and documentation. To analyze the results of research that uses techniques of data analysis based on interactive models Huberman and Miles. Whereas the examination of the validity of the data using the technique of prolongation of participation and triangulation.The results of this research show that the communication strategy used in Integrated service centres review of women and children (P2TP2A) city of Pekanbaru in mentoring young victims of sexual violence, the first komunikan already know the children victims of sexual assaults are reported through the terms of reference of each of the victims, namely the background and chronology of events, as well as the situation and conditions of child victims of sexual violence were reported. The aim of the communication messages are informative, persuasive and educative. Communication media used in the media through face-to-face counseling and supporting media using the media of drawing and coloring. While the role of the integrated services centre Communicator review of women and children (P2TP2A) the city of Soweto can be seen from the credibility and mentoring services.Keywords: Communication Strategies, Mentoring, Child Victims of Sexual Violence, Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) City of Pekanbaru